Formaldehyde Emission from Wood-Based Panels Bonded with Different Formaldehyde-Based Resins - Mohamed Salem (University of Zagreb, Faculty of Forestry and Wood Technology, 2011)
In this study, the formaldehyde emission (FE) from different types of particleboard, medium density fiberboard (MDF), and plywood products supplied from a commercial plant in the Czech Republic were evaluated by gas analysis (EN 717-2) and European small chamber (EN 717-1) methods. The significant effects of manufacturing variables (board type and thickness) as well as different types of formaldehyde-based resins on FE measured by gas analysis were obtained. When the E1 type adhesives were employed, a wide variation in the quantity of free formaldehyde was observed among the three product types. The FE values of plywood samples measured by gas analysis were lower than those of the particleboard and MDF samples. The correlation between the two methods for the particleboard and MDF were good (R2 = 0.82 and 0.76, respectively) and however for plywood (R2 = 0.52) it was not convincing. FE specifi ed in EN 717-2 was comparable with the EN 717-1 values for the same board type and thickness as well as the resin type and below the E1-emission class.